Political geography and corporate political strategy - Antia, Murad; Kim, Incheol; Pantzalis, Christos (Journal of Corporate Finance, 2013)
We examine the relationship between political geography and corporate political strategy by considering lobbying expenditures. We find that firms increase their lobbying intensity when local politicians cannot provide a direct link to the governing elite, i.e. when firm location on the political map shifts to an area that is not closely aligned with the president. Our results indicate that firm lobbying is a means for exerting influence on political power and is primarily geared toward building valuable political capital in order to exploit short-term opportunities. Lobbying expenditures are a matter of expediency for politically active firms that tend to spend less on lobbying when there is an alignment of power and more when there is misalignment of power. We also find that more sophisticated, better informed institutional investors recognize and/or encourage corporate political strategies that involve adjusting lobbying efforts in response to changes in political geography.